2010
DOI: 10.1016/j.jacc.2009.11.039
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Thromboembolism and Need for Oral Anticoagulation After Successful Atrial Fibrillation Ablation

Abstract: In this nonrandomized study, the risk-benefit ratio favored the suspension of OAT after successful AF ablation even in patients at moderate-high risk of TE. This conclusion needs to be confirmed by future large randomized trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
197
1
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 256 publications
(214 citation statements)
references
References 35 publications
11
197
1
5
Order By: Relevance
“…A number of studies, but not all, have reported a low stroke rate in patients who have undergone AF ablation when followed long term. 238,239,240,241,242 Although the results of these studies taken as a whole report a lower than expected stroke rate, these results can be considered preliminary data because many of these trials enrolled patients with a CHA 2 DS 2 -VASc score of <2, in whom stroke rates will be anticipated to be low. This reflects the fact that very few patients with a high stroke risk profile were followed long term after suspension of anticoagulation.…”
Section: Section 2: Definitions Mechanisms and Rationale For Af Ablmentioning
confidence: 89%
See 2 more Smart Citations
“…A number of studies, but not all, have reported a low stroke rate in patients who have undergone AF ablation when followed long term. 238,239,240,241,242 Although the results of these studies taken as a whole report a lower than expected stroke rate, these results can be considered preliminary data because many of these trials enrolled patients with a CHA 2 DS 2 -VASc score of <2, in whom stroke rates will be anticipated to be low. This reflects the fact that very few patients with a high stroke risk profile were followed long term after suspension of anticoagulation.…”
Section: Section 2: Definitions Mechanisms and Rationale For Af Ablmentioning
confidence: 89%
“…Multiple studies reported a low thromboembolic risk in patients who discontinued OAC after successful AF ablation. 238,406,407,408,409,410,411 However, an important limitation of these studies is the fact that only a small subset of patients had a CHA 2 DS 2 -VASc score ≥2, and almost no patients were at extreme increased stroke risk due to a prior stroke or TIA and/or age ≥75 years. Recent data from the German Ablation Registry 412 showed a high thromboembolic risk after ablation in high-stroke-risk patients.…”
Section: Section 4: Indicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Trwają kolejne próby kliniczne służące porównaniu nieprzerwanego leczenia za pomocą VKA i NOAC u pacjentów z AF poddawanych ablacji, np. wskazują na stosunkowo małą częstość występowania udarów mózgu w pierwszych kilku latach po ablacji przezcewnikowej AF [737,[771][772][773][774][775][776], to trzeba brać pod uwagę długotermino-we ryzyko nawrotu AF oraz profil bezpieczeństwa leczenia przeciwzakrzepowego u pacjentów po ablacji. Ze względu na brak danych z kontrolowanych prób klinicznych OAC po ablacji przezcewnikowej powinno być prowadzone zgodnie z ogólnymi zaleceniami niezależnie od domniemanych wyników leczenia pod względem utrzymywania rytmu zatokowego.…”
Section: Leczenie Przeciwzakrzepowe Przed Ablacją Podczas Ablacji I unclassified
“…Although retrospective studies have shown that discontinuation of warfarin therapy after catheter ablation may be safe over medium-term follow-up in some subsets of patients, there is insufficient evidence to recommend AF ablation for this indication. 7,8 It is recognised that recurrence of symptomatic or asymptomatic AF may be found during long-term follow-up after ablation. 6 For these reasons, discontinuation of warfarin or equivalent therapies is not a primary ablation indication.…”
Section: Asymptomatic Patientsmentioning
confidence: 99%